Deskripsi Kemampuan Motorik Halus Anak Melalui Kegiatan Finger Painting Bahan Alam Pada Anak Kelompok B TK YPK Pniel Malawele Kabupaten Sorong - Delila Itamar Moom; Yolan Marjuk; Ahmad Yulianto (Institut Nalanda, 2024)
Finger printing comes from English, involving the use of fingers as a tool to apply paint directly to a surface. This method allows children to freely express themselves by applying a mixture of colored paint to the designated area. The focus of this research is to determine the effect of finger painting activities with natural materials on the fine motor development of group B children at YPK Pniel Malawele Kindergarten, Sorong Regency. Utilizing a qualitative research approach, data collection methods include observation, interviews and documentation. Findings from observations and interviews conducted in Kindergarten showed that, among 10 children, 6 children showed a high level of fine motor skill development, while 4 children were at an early stage of development. This gap is caused by different levels of teacher guidance and attention, as well as irregular attendance in learning activities. Therefore, it can be concluded that finger painting activities, especially if facilitated effectively, can make a big contribution to improving fine motor skills in children.